Targeted eHealth Intervention to Reduce Breast Cancer Survivors' Fear of Recurrence: Results From the FoRtitude Randomized Trial. (31st May 2021) - Wagner, Lynne I; Tooze, Janet A; Hall, Daniel L; Levine, Beverly J; Beaumont, Jennifer; Duffecy, Jenna; Victorson, David; Gradishar, William; Leach, Joseph; Saphner, Thomas; Sturtz, Keren; Smith, Mary Lou; et al.
Abstract: Background: Fear of recurrence (FoR) is a prevalent concern among breast cancer survivors (BCS), yet few accessible interventions exist. This study evaluated a targeted eHealth intervention, "FoRtitude, " to reduce FoR using cognitive behavioral skills training and telecoaching. Methods: BCS (N = 196) were recruited from an academic medical center and 3 National Cancer Institute Community Oncology Research Program community sites, had stage 0-III breast cancer, were 1-10 years postprimary treatment, with moderate to high FoR and familiarity with the internet. Using the Multiphase Optimization Strategy, participants were independently randomly assigned to 3 cognitive behavioral skills (relaxation, cognitive restructuring, worry practice) vs an attention control condition (health management content [HMC]) and to telecoaching (motivational interviewing) vs no telecoaching. Website content was released across 4 weeks and included didactic lessons, interactive tools, and a text-messaging feature. BCS completed the Fear of Cancer Recurrence Inventory at baseline and at 4 and 8 weeks. Fear of Cancer Recurrence Inventory scores over time were compared using mixed-effects models. All statistical tests were 2-sided. Results: FCRI scores [SD] decreased statistically significantly from baseline to postintervention (T0 = 53.1 [17.4], T2 = 41.9 [16.2], P < .001). The magnitude of reduction in FCRI scores was comparable across cognitive behavior therapy (CBT) and attention control HMC conditions and was predicted by increased self-efficacy. Telecoaching was associated with lower attrition and greater website use (mean adherence score [SD] = 26.6 [7.2] vs 21.0 [10.5], P < .001). Conclusions: BCS experienced statistically significant reductions in FoR postintervention, but improvements were comparable between CBT and attention controls. Telecoaching improved adherence and retention. Future research is needed on optimal integration of CBT and HMC, dose, and features of eHealth delivery that contributed to reducing FoR. In the COVID-19 era, remote delivery has become even more essential for reaching survivors struggling with FoR.